1993
DOI: 10.1111/j.1348-0421.1993.tb01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Detection Methods for Legionella Species in Environmental Water by Colony Isolation, Fluorescent Antibody Staining, and Polymerase Chain Reaction

Abstract: Three detection methods for Legionella species in water samples from cooling towers and a river were examined. Direct counting of bacteria stained with fluorescent antibody (FA) for L. pneumophila (serogroups 1 to 6) could detect the cell of 104 to 106 cell/100 ml in all 14 samples, while colony counting method detected 10 to 103 CFU/100 ml only in 8 samples from cooling towers. Polymerase chain reaction (PCR) assay with primers to amplify 16S ribosomal DNA sequence of most Legionella species (LEG primer) dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 21 publications
2
43
0
1
Order By: Relevance
“…Furthermore, the methodological problems in the isolation of legionellae from environmental water can also contribute to an underestimation of culturable Legionella cells. The use of a selective medium and pretreat- ment by acid or heating reduce the cultivability (58). For all these reasons, it could be concluded that the culture methods underestimate the population of Legionella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the methodological problems in the isolation of legionellae from environmental water can also contribute to an underestimation of culturable Legionella cells. The use of a selective medium and pretreat- ment by acid or heating reduce the cultivability (58). For all these reasons, it could be concluded that the culture methods underestimate the population of Legionella.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods have also previously been developed to increase the rapidity of Legionella analysis. They are able to achieve a high degree of sensitivity and specificity without the need for a complex cultivation and additional confirmation steps (6,28,31,32,41,49,52,54,58). Some of these methods allow the detection of culturable and/or nonculturable Legionella within hours instead of the days required with the reference culture method.…”
Section: Discussionmentioning
confidence: 99%
“…A number of PCR-based assays have been developed for the detection and quantification of Legionella in water mainly using the 5S and 16S rRNA genes and the macrophage infectivity potentiator (mip) gene of L. pneumophila [23][24][25][26][27][28][29][30][31]. However, these assays lack the ability to discriminate between living and dead (non-infectious) Legionella cells.…”
Section: Introductionmentioning
confidence: 99%
“…These two methods cannot detect non-L. pneumophila spp. Although L. pneumophila is the most frequent cause of legionellosis, non-L. pneumophila species also may cause serious or fatal disease (16,24). Non-L. pneumophila species in respiratory specimens are not detectable by the L. pneumophila direct fluorescent antigen test.…”
mentioning
confidence: 99%